Nested PCR for ultrasensitive detection of the potato ring rot bacterium, Clavibacter michiganensis subsp. sepedonicus. - Lee, I M (1997)
Oligonucleotide primers derived from sequences of the 16S rRNA gene (CMR16F1, CMR16R1, CMR16F2, and CMR16R2) and insertion element IS1121 of Clavibacter michiganensis subsp. sepedonicus (CMSIF1, CMSIR1, CMSIF2, and CMISR2) were used in nested PCR to detect the potato ring rot bacterium C. michiganensis subsp. sepedonicus. Nested PCR with primer pair CMSIF1-CMSIR1 followed by primer pair CMSIF2-CMSIR2 specifically detected C. michiganensis subsp. sepedonicus, while nested PCR with CMR16F1-CMR16R1 followed by CMR16F2-CMR16R2 detected C. michiganensis subsp. sepedonicus and the other C. michiganensis subspecies. In the latter case, C. michiganensis subsp. sepedonicus can be differentiated from the other subspecies by restriction fragment length polymorphism (RFLP) analyses of the nested PCR products (16S rDNA sequences). The nested PCR assays developed in this work allow ultrasensitive detection of very low titers of C. michiganensis subsp. sepedonicus which may be present in symptomiess potato plants or tubers and which cannot be readily detected by direct PCR (single PCR amplification). RFLP analysis of PCR products provides for an unambiguous confirmation of the identify of C. michiganensis subsp. sepedonicus.